Characterising potential space suit textiles in proton beams using radiotherapy-based dosimetry. Issue 7 (1st October 2022) - Kuess, Peter; Sejkora, Nina; Klampfer, Anna; Madlener, Sarah; Weiss, Peter; Schmied, Sibylle; Georg, Dietmar; Özdemir-Fritz, Seda; Grömer, Gernot; Hirtl, Albert
Abstract: Four multi-layer textile samples for potential use in space suits, developed within the Planetary Exploration Textiles project of the European Space Agency, were exposed to a low energy proton beam, to characterise their effect on dose deposition in astronauts. Each textile stack contained all required layers for a potential space suit component. The influence of the textiles on proton beams was investigated using dosimetric equipment as utilised for medical purposes. The experiments were conducted at the synchrotron-based therapy and research centre MedAustron, Austria. To quantify the radiation characteristics, the water equivalent thickness of the fabrics was determined. A PEAKFINDER system (PTW, Freiburg, Germany) was positioned downstream of the textiles and the positions of the Bragg peaks were measured and compared to the range without any material in front. As reference values aluminium and lead plates were used and the results of the textiles were normalised to these materials. Furthermore, proton threshold energies for stopping protons in the suit materials were calculated. The position of the Bragg peak was shifted between 1.2mm to 2.6mm depending on the textile stacks. This corresponds to a proton threshold energy for the investigated stacks between 10–15MeV. The study showed that methods used in particle therapy are appropriate tools to quantify characteristics of space suit materials in proton beams. However, the effect of the investigated textiles on proton beams was comparable among the used fabrics.